A phase I study to assess safety, pharmacokinetics, and pharmacodynamics of a vaginal insert containing tenofovir alafenamide and elvitegravir - Thurman, Andrea R.; Ouattara, Louise A.; Yousefieh, Nazita; Anderson, Peter L.; Bushman, Lane R.; Fang, Xi; Hanif, Homaira; Clark, Meredith; Singh, Onkar; Doncel, Gustavo F. (Frontiers in Cellular and Infection Microbiology, 2023)
Background New multi-purpose prevention technology (MPT) products are needed to prevent human immunodeficiency virus (HIV) and herpes simplex virus type 2 (HSV2). In this study, we evaluated a fast-dissolve insert that may be used vaginally or rectally for prevention of infection. Objective To describe the safety, acceptability, multi-compartment pharmacokinetics (PK), and in vitro modeled pharmacodynamics (PD) after a single vaginal dose of an insert containing tenofovir alafenamide (TAF) and elvitegravir (EVG) in healthy women. Methods This was a Phase I, open-label, study. Women (n=16) applied one TAF (20mg)/EVG (16mg) vaginal insert and were randomized (1:1) to sample collection time groups for up to 7 days post dosing. Safety was assessed by treatment-emergent adverse events (TEAEs). EVG, TAF and tenofovir (TFV) concentrations were measured in plasma, vaginal fluid and tissue, and TFV-diphosphate (TFV-DP) concentration in vaginal tissue. PD was modeled in vitro by quantifying the change in inhibitory activity of vaginal fluid and vaginal tissue against HIV and HSV2 from baseline to after treatment. Acceptability data was collected by a quantitative survey at baseline and post treatment. Results The TAF/EVG insert was safe, with all TEAEs graded as mild, and acceptable to participants. Systemic plasma exposure was low, consistent with topical delivery, while high mucosal levels were detected, with median TFV vaginal fluid concentrations exceeding 200,000 ng/mL and 1,000 ng/mL for up to 24 hours and 7 days post dosing, respectively. All participants had vaginal tissue EVG concentrations of > 1 ng/mg at 4 and 24 hours post dosing. The majority had tissue TFV-DP concentrations exceeding 1000 fmol/mg by 24 – 72 hours post dosing. Vaginal fluid inhibition of HIV-1 and HSV-2 in vitro significantly increased from baseline and was similarly high at 4 and 24 hours post dosing. Consistent with high tissue TFV-DP concentrations, p24 HIV antigen production from ectocervical tissues infected ex vivo with HIV-1 significantly decreased from baseline at 4 hours post dosing. HSV-2 production from tissue also decreased post treatment. Conclusions A single dose of TAF/EVG inserts met PK benchmarks, with PK data supporting an extended window of high mucosal protection. PD modeling supports mucosal protection against both HIV-1 and HSV-2. The inserts were safe and highly acceptable. Clinical trial registration ClinicalTrials.gov, identifier NCT03762772.